Family functionality, depression and anxiety of adolescents in Tabasco, México - Loya-Valdez, Jesús Manuel; Becerra-Hernández, Antonio (Horizonte Sanitario, 2025)
Objective: To analyze the relationship between family dysfunction and symptoms of depression and anxiety in adolescents from two public schools in Tabasco.Material and methods: An observational and analytical study was conducted. The total sample was 256 adolescents from two public schools in Tabasco. Three scales were applied: APGAR (Adaptability, Partnership), Growth, Affection and Resolve) Family, Patient Health Questionnaire – 9 (PHQ-9) and Generalized Anxiety Disorder Scale – 7, with prior informed consent. In order to evaluate the relationship between family functionality and symptoms of depression and anxiety, Spearman correlations were performed. The value of p